2017
DOI: 10.1021/acs.energyfuels.6b02777
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Immobilized Recombinant Carbonic Anhydrase of Bacillus halodurans TSLV1 on the Surface of Modified Iron Magnetic Nanoparticles in Carbon Sequestration

Abstract: Carbonic anhydrase (CA) based conversion of CO2 to CaCO3 has been identified as a green and economic strategy to sequester CO2 from flue gas and industrial emissions. The method is, however, cost-intensive as an efficient immobilization method for reusing the enzyme poses a major challenge. In this investigation, the recombinant carbonic anhydrase of polyextremophilic bacterium Bacillus halodurans TSLV1 (rBhCA) has been immobilized on the surface of modified magnetic (silanized) iron oxide nanoparticles (Si-MN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…β-Glucosidase covalently immobilized on nanoparticle carriers has been studied by several authors [20,[27][28][29]. However, the use of mesoporous nanoparticles can lead to a number of advantages due to their high surface area and pore size [30]. The porous structure protects the enzyme against the harsh conditions of the reaction environment, such as high temperatures, extreme pH, and the presence of bubbles or inhibitors, creating an ideal micro-environment for the expression of the enzymatic activity [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…β-Glucosidase covalently immobilized on nanoparticle carriers has been studied by several authors [20,[27][28][29]. However, the use of mesoporous nanoparticles can lead to a number of advantages due to their high surface area and pore size [30]. The porous structure protects the enzyme against the harsh conditions of the reaction environment, such as high temperatures, extreme pH, and the presence of bubbles or inhibitors, creating an ideal micro-environment for the expression of the enzymatic activity [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, MNPs were dried under vacuum overnight at 60 °C. Surface modification of the dried MNPs was carried out using (3-aminopropyl)-triethoxysilane (APTES) as described by Faridi et al (2017). One gram of MNPs were dispersed in a mixture of 20% (w/v) APTES and 4 mL glycerol, and the resulting mixture was heated at 90 °C for 2 h under nitrogen sparging and stirring.…”
Section: Synthesis and Silanization Of Mnpsmentioning
confidence: 99%
“…Adsorption is a relatively simple method, however, leaching of the enzyme from the immobilized matrix after a few cycles limits its application (Sheldon and Woodley 2018). In contrast, covalent binding provides an advantage over the adsorption method by stabilising strong bonding between the enzyme and the matrix via a chemical reaction, thereby minimising enzyme leaching (Faridi et al 2017). Among the several immobilization matrices that have been studied, magnetic nanoparticles (MNPs) have proven to be a promising candidate for the immobilization of enzymes (Ranjan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also very easy and cost effective technique, which can be carried out simply in aqueous or organic media at moderate temperatures (Xu et al, 2014 ). Faridi et al ( 2017 ) showed that even after 22 cycles of reuse, recombinant α–CA (rBhCA) from B. halodurans TSLV1 immobilized on silanized iron MNPs (rBhCA-Si-MNPs) lost only 50% of activity. Nickel nanoparticles have been successfully used as a direct catalyst for CO 2 hydration reaction for assessing their application in CO 2 mineralization (Bhaduri et al, 2015 ).…”
Section: Carbon Capture and Storage (Ccs)mentioning
confidence: 99%